Direct access to functionalized 4-nitromethyl-chromenes via a domino reaction under catalyst-free conditions1. Issue 69 (29th July 2015) - Xu, Wengang; Li, Qingcui; Wang, Wangwang; Zheng, Hua; Zhang, Fanglin; Hu, Yunxing
<x xml:space="preserve">Abstract</x> A simple and practical tandem reaction has been established to synthesize functionalized 4-(nitromethyl)-4H-chromenes. Most products were obtained in medium to good yields. Further, chromeno[4, 3-b]chromene, an important structure, was easily obtained via this strategy.